Traces of The Socialist in Exile: Mohammad Hatta and Sutan Sjahrir - Farid, Muhammad (The Journal of Society and Media, 2020)
This paper aims to reveal the traces of the two national figures, Mohammad Hatta and Sutan Sjahrir during exile in Banda Naira. Both are warrior figures that are difficult to forget in the history of the nation. But their popularity was barely revealed during their exile in Banda Naira. In fact, the legacy of their thoughts and role models is needed to respond to the crisis of leaders who have morality and integrity for Indonesia, and at the same time respond to the challenges of the global era. This paper based on the results of qualitative-historical research, using a phenomenological perspective, especially on the narratives of everyday life of Hatta and Sjahrir in exile Banda. The results of this study indicate that Hatta and Sjahrir were both patriots and educators even they were far away in exile. They built an "Kelas Sore" for Banda children, teaching the values of everyday life, including; religious-ethics, self-integrity, and nationalism. These values are become valuable exemplary for todays young generation, and especially for the people of Banda Naira. This paper concludes, that Hatta and Sjahrir are the most consistent socialist role models in struggling and educating the people for sovereignty, and for a truly independent Indonesian nation